The Impact of Pricing and Promotional Strategies on Customer Satisfaction at A Hotel in Bandung - Qurotul Aini Annisa; Anton Tirta Komara; Haris Nurdiansyah; Imelda Megawati (P3M, Sekolah Tinggi Ilmu Ekonomi Pasundan Bandung, 2026)
This research investigates how pricing and promotional strategies influence customer satisfaction in the hospitality sector, specifically at a hotel in Bandung. It clarifies the relationships among these factors and provides actionable insights to enhance service quality and the customer experience. The study adopts a quantitative methodology, employing both descriptive and verificative approaches. To ensure a diverse representation, the sampling process utilizes a stratified random sampling method to select customers who have previously stayed at the hotel. This method yields targeted insights into customer perceptions across different demographics and experiences. The data collection process involves carefully designed questionnaires that solicit direct feedback on pricing, promotions, and overall hotel satisfaction. The findings reveal significant positive correlations between pricing and customer satisfaction, indicating that fair and competitive prices increase customer satisfaction levels. Similarly, effective promotional strategies, such as special deals and targeted marketing efforts, contribute to heightened customer satisfaction. The results show that customers appreciate both the service quality and the overall value they receive relative to prices and promotions. Furthermore, the study highlights that these two variables strongly drive overall customer satisfaction, emphasizing the importance of aligning pricing models and promotional activities to enhance the customer experience. The novelty of this research lies in its comprehensive quantitative analysis of pricing and promotions within the hotel industry, which fills a gap in the existing literature. Managers can leverage these insights to refine pricing models and enhance promotional efforts, thereby improving customer satisfaction, boosting loyalty, and strengthening the hotel's competitive market position.